Scientific Foundations of Audioloy : Perspectives from Physics, Biology, Modeling, and Medicine. - Cacace, Anthony T. (Plural Publishing, Inc, 2015)
Provides a strong basis and philosophical framework for understanding various domains of hearing science in the context of contemporary developments in genetics, gene expression, bioengineering, neuroimaging, neurochemistry, cochlear and mid-brain implants, associated speech processing and understanding, molecular biology, physics, modeling, medicine, and clinical practice.